Strategi Diksi dan Gaya Bahasa pada Media Publik Visual di Tembilahan - Mahsusi, Juni (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Visual public media in the form of banners in Tembilahan City are strategic communication media used by the government, business actors, and social organisations to target a diverse community. This study aims to conduct a qualitative analysis of the integrative strategy of diction and style in public visual banners in Tembilahan City to reveal the correlation between linguistic choices and the communicator's identity and discourse objectives. Based on an analysis of 20 purposively selected visual banner data, this study found three dominant strategy patterns, namely a formal instructional strategy with technical diction and an imperative style of language in government agencies. Furthermore, there is a commercial persuasive strategy with emotionally charged diction and a hyperbolic style of language in business actors. In addition, a collective emotional strategy was found, with inclusive diction and an exhortative style of language in social messages. In conclusion, the study found that the effectiveness of public visual communication is highly dependent on the strategic alignment between the accuracy of diction and the creativity of the style of language, which is adapted to the social position of the communicator and the context of the reader. Abstrak Media publik visual berupa spanduk di Kota Tembilahan merupakan media komunikasi strategis yang disampaikan pemerintah, pelaku usaha, dan organisasi sosial untuk menyasar masyarakat yang bervariasi. Penelitian ini bertujuan untuk melakukan analisis kualitatif strategi integratif diksi dan gaya bahasa pada spanduk visual publik di Kota Tembilahan untuk mengungkapkan korelasi pilihan linguistik dengan identitas komunikator dan tujuan wacana. Berdasarkan analisis terhadap 20 data spanduk visual yang dipilih secara purposif, penelitian ini menemukan tiga pola strategi yang dominan, yaitu strategi formal instruktif dengan diksi teknis dan gaya bahasa imperatif pada instansi pemerintah. Selanjutnya strategi persuasif komersial dengan diksi bernilai emosional dan gaya bahasa hiperbola pada pelaku usaha. Di samping itu, ditemukan strategi emosional kolektif diksi inklusif dengan gaya bahasa ekhsortasi pada pesan sosial. Kesimpulannya, penelitian menemukan bahwa efektivitas komunikasi visual publik sangat bergantung pada keselarasan strategis antara ketepatan diksi dan kreativitas gaya bahasa yang disesuaikan dengan posisi sosial komunikator dan konteks pembaca.